Perancangan Multimedia Virtual Tour Sebagai Media Informasi Mahasiswa Universitas Nusa Mandiri - Supriyadi Sandi (Jurnal Ilmu Komunikasi (J-IKA), 2022)
In line with the development of virtual reality technology which is very, very fast, based on the increase in technology, a new innovation application is formed, namely virtual tours. With virtual tours we can explore a location to get information and images about the place using only a laptop or cellphone, information kiosk or other electronic media, without having to bother going to the actual place. Currently, the means from the application of information about the rooms and facilities available at the University of Nusa Mandiri (UNM) which is one of the campuses in the East Jakarta area, namely Jatiwaringin, is still less communicative because it does not describe the place. Based on this problem, by creating a virtual tour application that was developed using a first person controller, it is hoped that it can provide information about the location of the rooms and facilities at the University of Nusa Mandiri (UNM) and provide a clearer picture of the place, without having to walk down every floor there is. on the campus building, by looking at this application, students are expected to understand the position and location of its existence according to their needs.